The possible use of coal fly ash and phosphate-solubilizing fungi for improving the availability of P and plant growth in acid soil - Retno Wilujeng; Gusti Irya Ichriani; F Fahrunsyah; Yulia Nuraini; Eko Handayanto (Brawijaya University, 2020)
The availability of P in acid soils may be raised through the application of phosphate solubilizing fungi (PSF). Coal fly ash (CFA) that has a high pH and contains a relatively high P may also be used to raise the availability of P in acid sois. The purpose of this study was to explore the possible use of CFA and PSF in a biochar-compost carrier to improve the availability of P and plant growth in acid soil. Combined applications of two PSF isolates (Aspergillus oryzae = F1, and Neosartorya fischeri = F2) carried in three levels of biochar-compost (80% biochar + 20% compost = B1, 70% biochar + 30% compost = B2, and 60% biochar + 40% compost =B3), and two doses of CFA (60 t/ha = C1, and 80 t/ha = C2) were tested in this study through two experiments. The results of experiment 1 (laboratory experiment) showed that the application of N. fischeri carried in 70% biochar + 30% compost combined with 80 t CFA/ha (F2B2C2 treatment) significantly increased the available P more than other treatments. In comparison with control, the increase of soil available P content ranged from 13% in the F1B1C1 treatment (A. oryzae in 80% biochar + 20% compost combined with 60 t CFA/ha) to 101% in the F2B2C2 treatment (N.fischeri in 70% biochar + 30% compost combined with 80 t CFA/ha). The results of experiment 2 (glasshouse experiment) showed that the highest dry weight of maize shoot was obtained by the F2B2C2 treatment that increased 123% compared to control. The highest P uptake by maize was obtained by the F2B2C2 treatment (N. fischeri in 70% biochar + 30% compost combined with 80 t CFA/ha).